Middlebrow Cinema - Faulkner, Sally (Remapping World Cinema, 2016)
"Middlebrow Cinema challenges an often uninterrogated hostility to middlebrow culture that frequently dismisses it as conservative, which it often is not, and feminized or middle-class, which it often is. The volume defines the term relationally against shifting concepts of 'high' and 'low', and considers its deployment in connection with text, audience and institution. In exploring the concept of the middlebrow, this book recovers films that were widely meaningful to contemporary audiences, yet sometimes overlooked by critics interested in popular and arthouse extremes. It also addresses the question of socially-mobile audiences, who might express their aspirations through film-watching; and traces the cultural consequences of the movement of films across borders and between institutions. The first study of its kind, the volume comprises 11 original essays that test the purchase of the term 'middlebrow' across cultures, including those of Europe, Asia and the Americas, from the 1930s to the present day. Middlebrow Cinema brings into view a popular and aspirational - and thus especially relevant and dynamic - area of film and film culture. Ideal for students and researchers in this area, this book: Remaps 'Popular' and 'arthouse' approaches Explores British, Chinese, French, Indian, Mexican, Spanish 'national' cinemas alongside Continental, Hollywood, Queer, Transnational cinemas Analyses Biopic, Heritage, Historical Film, Melodrama, Musical, Sex Comedy genres."